2022
DOI: 10.1111/aor.14428
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of systemic bivalirudin and sodium bicarbonate purge solution for Impella 5.5

Abstract: Background: Impella 5.5 (Abiomed; Danvers, MA) (IMP5) is a commonly used, surgically implanted, tMCS device that requires systemic anticoagulation and purge solution to avoid pump failure. To avoid heparin-induced thrombocytopenia (HIT) from unfractionated heparin (UFH) use, our program has explored the utility of bivalirudin (BIV) for systemic anticoagulation and sodium bicarbonatedextrose purge solution (SBPS) in IMP5.5. Methods: This single center, retrospective study included 34 patients supported on IMP5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Our routine practice is to provide systemic anticoagulation using bivalirudin along with sodium bicarbonate-dextrose purge solution in patients who are supported on Impella. 26 From 2019 to 2021, we observed a 10-fold increase in the utilization of Impella 5.0 and 5.5 at our institution. Compared to the smaller Impella devices (2.5 and CP), the larger devices (5.0 and 5.5) have improved designs to allow longer support duration, which enhances their use as a bridging modality to transplantation.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Our routine practice is to provide systemic anticoagulation using bivalirudin along with sodium bicarbonate-dextrose purge solution in patients who are supported on Impella. 26 From 2019 to 2021, we observed a 10-fold increase in the utilization of Impella 5.0 and 5.5 at our institution. Compared to the smaller Impella devices (2.5 and CP), the larger devices (5.0 and 5.5) have improved designs to allow longer support duration, which enhances their use as a bridging modality to transplantation.…”
Section: Discussionmentioning
confidence: 69%
“…Similar to other institutions, mechanical aortic valve and left ventricle thrombus preclude Impella utilization. Our routine practice is to provide systemic anticoagulation using bivalirudin along with sodium bicarbonate‐dextrose purge solution in patients who are supported on Impella 26 . From 2019 to 2021, we observed a 10‐fold increase in the utilization of Impella 5.0 and 5.5 at our institution.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The bicarbonate-based purge solution (sodium bicarbonate 8.4% 25 mEq in 1 L dextrose 5%) has been approved by the Food and Drug Administration in US as an alternative to heparin in patients with HIT. 20 Bashline et al 21 showed in their single center retrospective study including 34 patients supported with Impella that the use of systemic bivalirudin and bicarbonate-dextrose purge solution was associated with a rate of adverse events similar to the one previously reported with heparin. Recently, Al-Ayoubi et al 20 also showed the successful use of the bicarbonate–dextrose purge solution and bivalirudin for systemic anticoagulation in two patients with cardiogenic shock who developed HIT.…”
Section: Anticoagulation Management For Impellamentioning
confidence: 79%
“…In these cases, systemic anticoagulation can be achieved with the use of direct thrombin inhibitors (e.g., bivalirudin and argatroban), while intra-pump anticoagulation can be achieved using a bicarbonate-based purge solution. 20 , 21 The bicarbonate works by increasing the pH of the dextrose solution in the same way as heparin and prevents clot formation in the motor. The bicarbonate-based purge solution (sodium bicarbonate 8.4% 25 mEq in 1 L dextrose 5%) has been approved by the Food and Drug Administration in US as an alternative to heparin in patients with HIT.…”
Section: Anticoagulation Management For Impellamentioning
confidence: 99%